Hemagglutinin mutations related to antigenic variation in H1 swine influenza viruses. - Luoh, S M (1992)
The hemagglutinin (HA) of a recent swine influenza virus, A/Sw/IN/1726/88 (H1N1), was shown previously to have four antigenic sites, as determined from analysis of monoclonal antibody (MAb)-selected escape mutants. To define the HA mutations related to these antigenic sites, we cloned and sequenced the HA genes amplified by polymerase chain reaction of parent virus and MAb-selected escape mutants. The genetic data indicated the presence of four amino acid changes. After alignment with the three-dimensional structure of H3 HA, three changes were located on the distal tip of the HA, and the fourth was located within the loop on the HA. We then compared our antigenic sites, as defined by the changed amino acids, with the well-defined sites on the H1 HA of A/PR/8/34. The four amino acid residues corresponded with three antigenic sites on the HA of A/PR/8/34. This finding, in conjunction with our previous antigenic data, indicated that two of the four antigenic sites were overlapping. In addition, our previous studies indicated that one MAb-selected mutant and a recent, naturally occurring swine isolate reacted similarly with the MAb panel. However, their amino acid changes were different and also distant on the primary sequence but close topographically. This finding indicates that changes outside the antigenic site may also affect the site. A comparison of the HA amino acid sequences of early and recent swine isolates showed striking conservation of genetic sequences as well as of the antigenic sites. Thus, swine influenza viruses evolve more slowly than human viruses, possibly because they are not subjected to the same degree of immune selection.